IMPLEMENTATION OF RFID (RADIO FREQUENCY IDENTIFICATION) FOR STUDENT ATTENDANCE SYSTEM - -, Nurfiana; -, Putri (Prosiding International conference on Information Technology and Business (ICITB), 2015)
IBI Darmajaya is one of private university that located onBandar lampung which still use manual attendance.that isuse attendance book every time student come or leave theclass. This final report has a purpose to build anattendance system prototype that use a RFID technologywhich is integrated with arduino to increase the disciplineattitude program of student s honesty IBI Darmajaya.The prototype of RFID attendance system consist ofseveral main components such as tags and card that willbe used in KTM (Kartu Tanda Mahasiswa) and reader thatwill be used to read the information related to the studentattendance. The result of this final project is a prototype ofRFID for student attendance which has a function to storestudent s attendace data, with a maximum range 5cm anda minimum read 0,7 second to do an optimalfunctionability.KEY WORDS : Student Attendance System, RFID